Immune microenvironment features underlying the superior efficacy of neoadjuvant immunochemotherapy over chemotherapy in local advanced gastric cancer - Zhang, Ning; Li, Chunyu; Zhao, Zehua; Jiang, Biying; Wang, Wentao; Sun, Fujing; Zhang, Yong; Zhu, Yanmei (Frontiers in Immunology, 2025)
BackgroundThe therapeutic efficacy of neoadjuvant immunotherapy combined with chemotherapy (Io+Chemo) is superior than chemotherapy alone (Chemo). However, the mechanism of Io+Chemo superiority remains to be further elucidated.MethodsThe study included 128 patients with resectable stage II-III gastric cancer, in which 63 were given neoadjuvant Io+Chemo, and 65 Chemo alone. Patients given Io+Chemo were treated with 2-4 cycles of PD-(L)1 inhibitor (Pembrolizumab, Sintililimab or Nivolumab) with S-1 and oxaliplatin (SOX) or capecitabine and oxaliplatin (XELOX) before surgical resection. Patients given Chemo were treated with 2-4 cycles of SOX or XELOX before surgical resection. Tumor tissues were evaluated for tumor-infiltrating immune cells (TIICs) using immunohistochemistry and QuPath software quantitative analysis, for detecting T, B, NK, plasma cells, and macrophages. The relationship between TIICs and different neoadjuvant treatment regimens and pathological responses was also explored.ResultsCompared with Chemo, Io+Chemo induced higher rates of pathological complete response (33.3 vs. 9.2%, p=0.001) and major pathological response (MPR) (49.2 vs. 30.8%, p=0.033). Compared with Chemo group, density of CD4+(1904.8 vs. 1530), CD8+(1982.9 vs. 1124.4), CD20+(1115.6 vs. 574), CD38+(1580.4 vs. 1128), CD138+(1237.2 vs. 496.4), and CD56+ (596.8 vs. 159) cells was increased 24.5%, 76.4%, 94.4%, 40.1%, and 149.2% respectively, whereas CD163+ macrophages (994.4 vs. 1706) was decreased 41.7% in Io+Chemo group.ConclusionsOur study favors neoadjuvant Io+Chemo over Chemo and reveals Io+Chemo can induce the formation of an immune-activated microenvironment that make Io+Chemo superior to Chemo.